Incidencia de la inteligencia Emocional a partir de los Lenguajes Artisticos - Diana Marcela Rodriguez; Maria Angelica Carrillo; Luz Angela Gomez R. (Pensamiento Palabra y Obra, 2010)
This article was prepared as one of the topics of the research project “Impact of Emotional Intelligence starting from artistic languages in the pedagogical practices at the school”. It is intended to present some of the reflections of the work team issued in the course of the research process, concerning the inclusion of emotional intelligence and artistic languages in pedagogical and life experiences of teachers from the Capital District. It becomes our challenge to think about the theoretical approaches regarding the relationships: emotion-cognition, emotional intelligence-school, school-art-emotion, artistic languages-school, as well as about the role they play in the production of new knowledge and the methodological entries that are being generated in educational research to understand these processes.We are aware that artistic languages and emotional intelligence, when they are viewed through a pedagogical approach, may well constitute scenarios of recognition and transformation not only for pedagogical practices, but even for the human being who learns, teaches and lives daily the encounter with knowledge.